Seasonal variation in composition and characteristics of indian municipal solid waste –A case study - Agrawal, Anita; Pandey, Rama; Agrawal, M L (Recent Research in Science and Technology, 2013)
<span style="font-size: 10.0pt; line-height: 115%; font-family: "Arial Narrow","sans-serif"; mso-fareast-font-family: BatangChe; mso-bidi-font-family: "Times New Roman"; mso-font-kerning: 1.0pt; mso-fareast-language: KO; mso-bidi-font-weight: bold;">In developing countries like India, rapid urbanization and uncontrolled population growth have lead to the socio-environmental problem of ill-managed municipal solid waste. Evaluating the characteristics of municipal solid waste is an important aspect of MSWM because the selection of effective management strategies depends on the types and variation in the characteristics of the waste to be managed. The focus of the present paper is to determine the variation in composition as well as characteristics of municipal solid waste for Indian conditions. A case study is presented for Raipur city to determine the seasonal variation in waste characteristics. The seasonal variation in characteristics of MSW was found to be in a wide range of 4-125 %, so for comprehensive management of this MSW, a proper combination of recycling and recovery, composting, energy generation and dumping on land should be adopted.